39 Endometrial cancer incidence rise: a case of overdiagnosis?. (8th June 2022) - Barmayehvar, Behrad; Oke, Jason; Behzadnia, Alireza; Nicholson, Brian; Zahl, Per-Henrik; Roberts, Nia
Abstract : Objectives: Over the last two decades, the incidence of endometrial cancer has risen by 55% whilst its mortality has been stable. 1 These trends have raised concerns that the increase in the incidence of endometrial cancer may be due to overdiagnosis. In this study, we explored the potential for overdiagnosis, drawing on the criteria proposed by Welch and Black, 2 looking to establish whether there is: 1) a reservoir of previously undetected disease and 2) changes in diagnostic practice that would lead to detection of the disease reservoir. Method: A systematic review and meta-analysis of autopsy case series of posthumously discovered endometrial cancers in asymptomatic women was performed using MEDLINE, EMBASE and Web of Science databases to investigate the endometrial cancer reservoir. Risk of bias was assessed using the GRADE framework for prevalence studies. Rapid review of the literature, snowballing search and expert opinion from academic gynaecologists were used to explore the changes in clinical practice. Population level, stage specific incidence data by region and age of diagnosis for the period 1960 -2009 was obtained from Norway along with data on ultrasound use between 2006 – 2009 by region. Trends in incidence by stage, and age of diagnosis of endometrial cancer from Norway were analysed using linear regression. Changes in incidence (from 2006–2009) and the number of ultrasound scans (USS) performed was analysed using correlation to quantify the strength of association between changes in diagnostic practice incidence over time. Results: From 1, 014 studies identified, three studies met our inclusion criteria with one study providing estimates from two separate cohorts. From a total of 9, 348 autopsies, 25 had evidence of asymptomatic endometrial cancer. The pooled prevalence of asymptomatic endometrial cancer was 290 per 100, 000 women with heterogeneity of I 2 = 13%. The overall quality of studies was moderate. Regression analysis showed that the increase in incidence was driven by localised endometrial cancer in post-menopausal females during the 1960–2009 period. Pearson's product-moment correlation of USS numbers per annum and incidence rate revealed a strong positive correlation (r = 0.90, p = 0.09). Conclusion: Our review uncovered the existence of an indolent pool of disease, although the extent of evidence is limited precluding us from making strong conclusions. The disproportionate incidence rise of localised cancers in Norway provides additional support for the overdiagnosis hypothesis, which appears to be associated with a corresponding rise in USS. Nevertheless, the dynamic changes in incidence figures are likely to be multifactorial, with changing diagnostic practices and population-wide risk factors both interacting. References: Uterine cancer statistics [Internet]. Cancer Research UK. 2020 [cited 18 July 2020]. Available from: https://www.cancerresearchuk.org/health-professional/cancer-statistics/statistics-by-cancer-type/uterine-cancer Welch H, Black W. Overdiagnosis in cancer. JNCI Journal of the National Cancer Institute 2010;102 (9):605–613.